2019
DOI: 10.1002/maco.201910974
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface treatment on the corrosion behavior of a pure Ta sheet in an equimolar NaCl–KCl melt at 850°C in air. Part 1: Laser surface melting

Abstract: The corrosion behavior of pure Ta and laser surface melting-treated Ta sheets was investigated in an equimolar NaCl-KCl melt at 850°C in air. The results show that the predominant factors involved in the consumption of materials were reactions that form sodium-containing oxides and Ta 2 O 5 . High corrosion stress led to slip of the untreated Ta surface grains, further resulting in preferential corrosion along slip bands. The slip of surface grains substantially deteriorated the bonding between the corrosion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Among the candidate elements, Ta displays great potential as a substitute for Cr to improve the oxidation and hot corrosion resistance of NiAlY coatings. [8,9] George et al [10] proposed the beneficial effect of Ta for the hot corrosion resistance of Ni-based superalloys exposed to Na 2 SO 4 at 900°C and 1000°C. Robin and Rosa [11] found that the Ta improved the corrosion resistance of Nb-based alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Among the candidate elements, Ta displays great potential as a substitute for Cr to improve the oxidation and hot corrosion resistance of NiAlY coatings. [8,9] George et al [10] proposed the beneficial effect of Ta for the hot corrosion resistance of Ni-based superalloys exposed to Na 2 SO 4 at 900°C and 1000°C. Robin and Rosa [11] found that the Ta improved the corrosion resistance of Nb-based alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we use an immersion method as a one-pot reaction to deal with the lithium metal-containing coin cell waste. In our method, the sealing-breaking as a prerequisite process is accelerated by the chloride corrosion of the stainless-steel cell case. At the same time, water involves the gradual and controllable conversion of Li and HF to LiOH and LiF. We proposed that 0.5 M FeCl 3 aqueous solution is the optimized choice for coin cell waste management by comparing the corrosion of bare coin cell cases and half-cells in the medium of FeCl 3 , cupric chloride (CuCl 2 ), and sodium chloride (NaCl).…”
Section: Introductionmentioning
confidence: 99%